2020
DOI: 10.1161/jaha.120.017728
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Different Fruit and Vegetable Sources With Incident Cardiovascular Outcomes: A Systematic Review and Meta‐Analysis of Prospective Cohort Studies

Abstract: Background Public health policies reflect concerns that certain fruit sources may not have the intended benefits and that vegetables should be preferred to fruit. We assessed the relation of fruit and vegetable sources with cardiovascular outcomes using a systematic review and meta‐analysis of prospective cohort studies. Methods and Results MEDLINE, EMBASE, and Cochrane were searched through June 3, 2019. Two independent reviewers extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
76
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(90 citation statements)
references
References 164 publications
9
76
0
5
Order By: Relevance
“…Total decreases of 9.3% in total cholesterol, 12.9% in low-density lipoprotein and 10.5% in triglycerides have been reported in a meta-analysis of 38 research studies where on the average 50 g of soy protein was taken daily [ 104 ]. Similar decreases were observed in other studies demonstrating decreases in cholesterol, LDL and triglycerides [ 105 , 106 , 107 , 108 , 109 ]. However, the data are contradictory, and several meta-analysis studies reported no isoflavone-induced changes in serum lipid profile [ 84 , 110 ].…”
Section: The Role Of Isoflavones In Chronic Degenerative Diseasessupporting
confidence: 90%
“…Total decreases of 9.3% in total cholesterol, 12.9% in low-density lipoprotein and 10.5% in triglycerides have been reported in a meta-analysis of 38 research studies where on the average 50 g of soy protein was taken daily [ 104 ]. Similar decreases were observed in other studies demonstrating decreases in cholesterol, LDL and triglycerides [ 105 , 106 , 107 , 108 , 109 ]. However, the data are contradictory, and several meta-analysis studies reported no isoflavone-induced changes in serum lipid profile [ 84 , 110 ].…”
Section: The Role Of Isoflavones In Chronic Degenerative Diseasessupporting
confidence: 90%
“…However, no other significant effects on other markers of CVD risk were found. This is supported by a SRMA of more than 80 cohort studies which followed up 4,031,896 individuals for an average of 11 years [68]. During that time, more than 125,000 cardiovascular events were recorded.…”
Section: Cardiovascular Healthmentioning
confidence: 80%
“…Current dietary guidelines advocate beneficial patterns that share several key characteristics, including abundant intakes of fruits, vegetables, nuts and seeds, legumes, and whole grains, as well as seafood, yogurt, and vegetable oils, while minimizing the intake of red and processed (sodium/nitrate-preserved) meats, refined grains, starches, and added sugars [ 3 , 5 ]. Fruits and vegetables (e.g., citrus, berries, apples, cruciferous and green leafy vegetable sources) are rich in many essential nutrients and other bioactive compounds that can provide protection against many chronic diseases [ 6 , 7 ]. Dietary recommendations promote the consumption of at least five to nine servings of a variety of fruits and vegetables per day in a 2000 kcal diet [ 3 , 5 ], which provide abundant amounts of vitamins (e.g., ascorbic acid, folate, pro-vitamin A), minerals (e.g., potassium, calcium, and magnesium), fibers, and a diversity of bioactive phytochemicals such as polyphenols (e.g., flavonoids and phenolic acids) and carotenoids (e.g., carotenes and lycopene) [ 8 ].…”
Section: Introductionmentioning
confidence: 99%